Intraoperative indocyanine green fluorescence cholangiography can rule out biliary atresia: A preliminary report - Shirota, Chiyoe; Hinoki, Akinari; Togawa, Takao; Ito, Shogo; Sumida, Wataru; Makita, Satoshi; Amano, Hizuru; Takimoto, Aitaro; Takada, Shunya; Okamoto, Masamune; Nakagawa, Yoichi; Kato, Daiki; et al. (Frontiers in Pediatrics, 2022)
Background: The prognosis of BA is known to be poor if definitive surgery is performed too late. Therefore, excluding BA as a diagnosis at an early stage is crucial. Conventional cholangiography requiring cannulation through the gallbladder may be unnecessarily invasive for patients, especially when ruling out BA. Therefore, a less invasive alternative such as indocyanine green (ICG) cholangiography, which does not require cannulation, should be established. In this study, we focused on excluding BA and confirmed the usefulness of intravenous ICG fluorescence cholangiography. To the best of our knowledge, this is the first preliminary study to report the use of intravenous ICG cholangiography for BA exclusion. Methods: The study participants were patients who underwent liver biopsy and intraoperative cholangiography after they were suspected to have BA, between 2013 and 2022. ICG fluorescence cholangiography was performed on all patients who provided informed consent. Results: During the study period, 88 patients underwent a laparoscopic liver biopsy and cholangiography. Among them, 65 (74%) were diagnosed with BA and underwent a subsequent laparoscopic Kasai portoenterostomy. BA was ruled out intraoperatively in 23 patients. Of the 23 patients in whom BA was ruled out, 14 underwent ICG cholangiography, 11 had gallbladder (GB) fluorescence, and 9 had both GB and common bile duct (CBD) fluorescence. Conventional cholangiography was very difficult in 2 of 23 cases: in 1 case, cannulation of the atrophic gallbladder was impossible, and cholecystectomy was indicated after multiple attempts; in 1 case, upstream cholangiography was not possible. In both cases, ICG fluorescence cholangiography successfully imaged the CBD and the GB. Conclusions: In conclusion, intravenous ICG fluorescence cholangiography might be a useful and less invasive diagnostic procedure that can rule out BA in infants.